PENGARUH PEMBERITAAN AKSI BELA ISLAM TERHADAP KONSTRUKSI HIERARKI MEDIA BERITA SATU - Nurul Zakiah; Dian Ariyani Hi. Umar (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2021)
The research problem formulation about the news contents of “islamic defense action” in Berita Satu, consist of the major question and theminor question. The major question in this study is to know how the Islamic defense movement in the construction of the influence hierarchyin Berita Satu is reported. Meanwhile, the minor questions are to know how far the influence level of individual worker in reporting the Islamicdefense movement in Berita Satu, the elements in the media routine that affect the news content of the Islamic defense movement in Berita Satu,the influence of media organizations in the news content in Berita Satu, the ideology adopted by the television station of Berita Satu that affectsthe content of the news. The main theory used in this study is the Hierarchy Theory of the Influence of Media Content by Pamela J.Shoemaker and Stephen D. Reese. This theory states that the content of media coverage is influenced by five levels, namely individual level,media routines level, organizational level, extra media level, and ideological level. The results of this study indicate that the media is notonly a means of information provider, but the media is also used as abusiness institution. As a result, the content of the news about the Islamicdefense movement in BeritaSatu has been influenced by various elements including the five elements in the Influence Hierarchy Theory of MediaContents. The elements that have a significant influence on the content of the news are the elements of the organization or the influence of theowner of Berita Satu, namely Lippo Group, and the ideology of Berita Satu is Pancasila. In conclusion, Berita Satu constructs the contents ofthe news about Islamic defense movement by building multilevel influences starting from the level of individual workers, media routines,organizations, media extras such as news sources, advertisers, and the government, as well as applying the ideology adopted into the news.